Investigating the Effect of Reducing the Signs and Symptoms of Lid Wiper Epitheliopathy in Patients With Dry Eye Disease With Perfluorohexyloctane - Chris Lievens, OD, MS, PhD, FNAP, FAAO; Andrew D. Pucker, OD, PhD, FAAO; Quentin Franklin, BS; Stephen M. Montaquila, OD, FAAO; Brad Giedd, OD, MS, FAAO; Gina Wesley, OD, MS, FAAO; Morgan Bromley, PhD; Zackarias Coker, MS; John Meyers, MS; Marta Vianya-Estopa, PhD (Current Therapeutic Research)
ABSTRACT: Background: Perfluorohexyloctane (PFHO) acts to prevent the evaporation of the tear film. It has the potential to limit friction related issues between the eye lid margin and the ocular surface. Prior to the present work, this had not yet been evaluated. Objective: To examine the potential of using perfluorohexyloctane for reducing the signs and symptoms of lid wiper epitheliopathy (LWE). Methods: Data were collected at 4 visits spanning 2 months. Patients who had symptomatic dry eye and a LWE score of ≥1.0 on the Korb LWE scale were recruited. Participants were randomized to PFHO 4 times a day or no treatment. Lid wiper epitheliopathy was graded at each visit with the Korb and photographic LWE (PLWE) scales. Symptoms were assessed using the Standard Patient Evaluation of Eye Dryness questionnaire and visual analog scales (0–100). Results: A total of 52 participants were enrolled (mean ± SD age, 49.7 ± 15.7 years; 79% female). Right eyes in the treatment group were significantly more likely to show an improvement of ≥0.5-units in PLWE scores at 2 months than the no treatment group (P = 0.04), but no left eye differences were noted. Korb and PLWE scores were significantly better in the treatment group compared with the no treatment group starting at 2 weeks and remained so for the duration of the study (all P < 0.001). Standard Patient Evaluation of Eye Dryness scores and dry eye symptoms were significantly better in the treatment than in the no treatment group at the 2-month visit (all P ≤ 0.01). Conclusions: Perfluorohexyloctane significantly reduced LWE and improved dry eye symptoms compared with no treatment, suggesting that PFHO may enhance ocular lubrication and reduce friction-related damage. Masked, randomized, trials are still needed to compare PFHO to other treatments in participants with LWE to support generalizability of results. ClinicalTrials.gov study NCT06671041.